2022
DOI: 10.1097/anc.0000000000001036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Premature Infant Oral Motor Intervention on Sucking Capacity in Preterm Infants in Turkey

Abstract: Background: Preterm infants have oral feeding difficulty that often delays discharge, indicating a need for evidence-based interventions for oral–motor development. Purpose: To test the Premature Infant Oral Motor Intervention (PIOMI) on the development of oral–motor function, feeding, and anthropometric outcomes using sucking manometry. Methods: A single-blind randomized experimental design was conducted with a sample of 60 preterm infants from 2 neonatal intensive care units between May 2019 and March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Similarly, Arora et al ( 5 ) reported that neonates receiving PIOMI could be discharged earlier as compared to sham intervention (P > 0.05). Some of the other studies have observed a statistically significant reduction in the duration of stay with PIOMI, however, the control groups in these studies had not received any form of oral motor stimulation ( 4 , 6 , 8 , 12 , 14 16 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Arora et al ( 5 ) reported that neonates receiving PIOMI could be discharged earlier as compared to sham intervention (P > 0.05). Some of the other studies have observed a statistically significant reduction in the duration of stay with PIOMI, however, the control groups in these studies had not received any form of oral motor stimulation ( 4 , 6 , 8 , 12 , 14 16 ).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Arora et al (5) reported that neonates receiving PIOMI could be discharged earlier as compared to sham intervention (P > 0.05). Some of the other studies have observed a statistically significant reduction in the duration of stay with PIOMI, however, the control groups in these studies had not received any form of oral motor stimulation (4,6,8,12,(14)(15)(16)). Although the difference between the groups for oral feeding readiness, full oral feeding, and duration of hospitalisation was not statistically significant, each day saved in terms of clinical management has a significant implication on the expenditure for the affected family and the healthcare system.…”
Section: Discussionmentioning
confidence: 94%
“…Third, outcome measures and indices varied across the included studies; therefore, we could only compare the OMI and NNS groups in terms of transition time, hospitalization duration, and weight gain. We did not assess other relevant outcomes, such as the Preterm Oral Feeding Readiness Assessment Scale scores [19,23], sucking power [22], or volume and rate of milk intake [19,22,23]. Finally, the included studies tended to exclude preterm newborns with complications or respiratory, cardiovascular, neurological, and digestive disorders; however, these newborns constitute an important proportion of preterm infants with pediatric feeding disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that episodes of apnea, bradycardia, or oxygen desaturation during the oral feeding session were recorded. However, there is no specific mention of the frequency of these complications or if there was any significant difference between the intervention and control groups regarding these episodes [22,25]. One study did not specifically mention complications such as apnea, desaturation, or aspiration within this document [20].…”
Section: Complicationmentioning
confidence: 99%
See 1 more Smart Citation